The Function of Humor Applied in Margaret Chos Stand-Up Comedy: PsyCHO - Anindita Dewangga Puri; F.X. Risang Baskara (Universitas Sanata Dharma, 2019)
This article discusses the function of humor in Margaret Cho's Stand-Up Comedy entitled PsyCHO. The aims of this research are to explain the humor function applied by Margaret Cho in creating humor situation in her stand-up comedy. The data in this research are oral data which is transcribed into written form. This study uses a qualitative descriptive method. According to the research in the stand-up comedy entitled PsyCHO, the researchers found that Margaret Cho tends to use humor function to create solidarity with the audiences. This is dominated by sharing strategy which is often conveyed by Cho in her stand-up comedy. Keywords: humor, stand-up comedy, pragmatics, jokes